Hemorrhage after Stereotactic Biopsy from Intra-Axial Brain Lesions: Incidence and Avoidance - Shakal, Ahmed Abdel Sallam; Mokbel, Esam Abdel Hay (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background With the introduction of stereotactic surgery in humans by Spiegel and Wycis in 1947 and the great advances in neuroimaging, image-guided stereotactic brain biopsy is the mainstay for diagnosis of intrinsic deep-seated brain lesions. Stereotactic biopsy is usually safe, and the reported rate of complications is minimal, with mortality being reported in less than 1% and significant morbidity occurring in less than 5%. The complication most often encountered after stereotactic biopsy is hemorrhage.Patients and Methods A total of 150 patients (84 male and 66 female) with the mean age of 52.8 years having intra-axial brain lesions were included in the study. Image-guided (114 computed tomography [CT] and 36 magnetic resonance imaging [MRI]) stereotactic biopsy were performed by a specialized stereotactic neurosurgeon. Routine preoperative coagulation studies were performed in all patients. A workstation with multiplanar trajectory planning software was used. Serial biopsies were done with Sedan-type side cutting needle. Any detectable bleeding was analyzed by CT within 4 hours after procedure. All medical charts, laboratory results, preoperative imaging studies, and postoperative imaging studies were reviewed.Results A conclusive histopathological diagnosis was achieved in 147 patients (98%). In 7 patients (4.7%), hemorrhage was detected in post-biopsy CT scan (3.3% asymptomatic and 1.4% symptomatic). Hemorrhage occurred in patients with highly malignant tumors. There was no mortality.Conclusion Using multiplanar image-guided trajectory planning and a small biopsy needle decreases the incidence of post-biopsy hemorrhage. Neurologically intact patients with no hemorrhage in post-biopsy CT scan could safely be discharged home at the same operative day.
Keywords: stereotactic biopsy; intra-axial brain lesions; complications; hemorrhage